Correlation between Arm Position, Craniovertebral Angle, and Non-Specific Neck Pain in College Students - Rossa, Melya; nugraha, afif dwi; Antoni, Muhamad Fauzi; Andriana, Laily Mita; Putra, Dani Pramuno; Yudhistira, Dewangga (Universitas Negeri Semarang, 2024)
Students, especially intensive users of visual devices such as computers, are at risk of postural disorders such as Forward Head Posture (FHP) and non-specific neck pain (NSNP). The static position of the arm is thought to contribute to this disorder. This study used a cross-sectional design with 47 female participants aged 18-25 years. FHP is measured by Craniovetebral Angle (CVA), static position of the arm with Forward Shoulder Angle (FSA), and neck pain with Neck Disability Index (NDI). Data analysis was carried out by the Pearson correlation test. The results showed that there was no significant relationship between CVA and FSA (r=0.182; p>0.05), but there was a significant negative relationship between FSA and NDI (r=-0.315; p<0.05). The conclusion was that there was no association between FHP and static arm position, but there was an association between static arm position and non-specific neck pain.